LEADING THE DIGITAL SHIFT: EXPLORING TRANSFORMATIONAL LEADERSHIP IN MADRASAH REFORMS - Herdiaty, Intan Shella; Widjaja, Anton Wachidin (President University, 2024)
This study explores the impact of digital transformation on madrasah reform in Indonesia, focusing on how transformational leadership, collaborative culture, and organizational learning contribute to institutional performance. A mixed-method approach was used, combining quantitative surveys and qualitative interviews with madrasah leaders across Indonesia. The survey examined the relationship between digital transformation and madrasah performance, while the interviews provided insights into leadership and collaboration practices influencing reform. The study finds that digital transformation positively impacts madrasah performance, particularly when supported by transformational leadership and a strong collaborative culture. Transformational leaders play a crucial role in motivating staff to embrace digital tools and fostering a learning-oriented environment. Organizational learning and collaborative practices enhance the success of digital initiatives, ensuring effective reform.The research is limited to madrasahs in Indonesia, focusing primarily on institutional leaders. The findings may not be fully generalizable to other educational systems or cultural contexts. The study contributes to the literature on educational reform by highlighting the importance of digital transformation in Islamic educational institutions. It extends transformational leadership theory by applying it to the context of madrasah reform. Madrasah leaders should foster collaborative cultures to support digital transformation, ensuring that reforms align with both academic and religious goals. This research is one of the few studies examining digital transformation in Islamic educational institutions, offering valuable insights into how leadership and culture drive successful reform.